Integrasi Wisata Halal dan Pemberdayaan Pesantren dalam Pengabdian kepada Masyarakat: Sebuah Model Pembangunan Sosial dan Spiritual - Bin Noh Seth, Muhammad Najib; Sentosa, Ilham; Prasetyanto, Hermawan; Yulianto, Gunawan; Santoso, Agus Wibowo Setyo Budi; Sugesti, Sahlit; Nugroho, Setyo Prasiyono; Susilowati, Heni; Damasdino, Fian; Hermawan, Hary; Widagda, Sidiq Pramana (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
Integration of Halal Tourism and Pesantren Empowerment in Community Service: A Model for Social and Spiritual Development. This community service program aims to develop a pesantren-based halal tourism model by establishing a professional social homestay at PPPA Raudhatul Jannah, Bantul. The initiative is strategically designed to enhance financial sustainability, enabling free Qur'anic education for underprivileged students and orphans. Utilising a participatory engagement approach, the program involves academics, administrators, and residents. Key implementation steps include homestay management assistance, integration of intensive tahfidz programs, and local economic empowerment through traditional halal culinary activities. Results indicate that the social homestay model serves as a viable, sustainable funding mechanism while strengthening the pesantren's role as an inclusive centre for da'wah and community empowerment. This integrated approach transforms the institution into a faith-based social enterprise. Furthermore, this model contributes to halal tourism grounded in spiritual values and fosters opportunities for international academic collaboration to support the broader dissemination of Islamic values.